Effect of Exercise on Quality of Life in Parkinson’s Disease: A Systematic Review and Meta-Analysis - Kui Chen; Yan Tan; You Lu; Jiayan Wu; Xueyuan Liu; Yanxin Zhao (2020)
Exercise has an integral impact on the physical and mental wellbeing of patients with Parkinson's disease (PD), yet no comprehensive and quantitative analysis has been conducted on the effect of exercise on quality of life (QoL) in these patients. This study aimed to evaluate the effect of exercise on overall QoL and different domains of QoL in people with PD, as well as investigating the influence of factors such as the exercise type and intervention period.Databases, such as PubMed, Embase, and Cochrane Central Register of Controlled Trials, were searched since inception to August 14, 2018 to identify randomized controlled trials that compare the effect of exercise versus no intervention on QoL in PD patients. Following the subgroup analysis, heterogeneity was further explored. The quality of eligible studies was assessed according to PRISMA guidelines.20 studies were included with 1,143 participants in total. A meta-analysis showed a significant improvement in QoL after exercise intervention in PD patients (SMD = -0.24, 95% CI = -0.36 to -0.12, P < 0.001). A subgroup analysis of exercise types revealed significant QoL improvement with aerobic exercise, martial arts, and dance, but not anaerobic exercise and combined exercise. Interventions lasting 12 weeks or longer improved QoL significantly.Exercise interventions, especially aerobic exercise, dance, and Tai Chi, significantly improve QoL in PD patients. At least 12 weeks of exercise is needed to bring about significant benefits.